ANALISIS KONTRIBUSI SEKTOR PERIKANAN KABUPATEN SIKKA PROVINSI NUSA TENGGARA TIMUR - Ferdinandus Kaiso; Barnabas Pablo Puente Wini Bhokaleba (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2021)
Sikka Regency has enormous resources and biodiversity. The aims of this study are (1) to analyze the potential of fisheries in Sikka Regency, (2) to analyze the contribution of the fisheries sector to GDP in Sikka Regency. This research was conducted from 26 August 2019 to 26 September 2019 in Sikka Regency, East Nusa Tenggara Province. The method use is descriptive qualitative research. Primary data were obtained through interviews with selected informants, while secondary data included data on fishing catch and aquaculture production, and GDP of Sikka Regency for the last 5 years. Data analysis using Shift Share and Location Quotient methods. The results of the study indicate that the fishing catch and aquaculture sectors are very potential in supporting the regional economy. The average of fisheries catch production is 14,689 tons (20%) and the average production value obtained is Rp 150,069,556 (26%). The average contribution value of the fishery sector is 30.13%, while the value of the contribution of the fisheries sector on the basis of constant prices is 29.70%. The LQ value based on current prices is 6.304 and the LQ value based on constant prices is 6.462 making the fisheries sector in Sikka Regency the basis sector.